Sosialisasi Dan Praktik Cuci Tangan Pakai Sabun Dalam Perilaku Hidup Bersih Dan Sehat - Muhammad Syamsi; Luthfia Al Azizah; Nida Nadhifatul Jannah; Mulkan Habibi (Jurnal Pelayanan Hubungan Masyarakat, 2023)
As KKN participants, we must be able to adjust to the reality. We do not only understand theory, but we must be able to apply and learn from the experiences that we have in the community. From this experience, we can make our thinking more mature. Through this KKN program, students are expected to be introduced directly to social life directly with all its problems. By finding problems in society, students are required to find solutions through the mechanisms of their respective scientific interdisciplinary work systems.